The Role of The Financial Services Authority (OJK) as A Supervisor in Digital Financial Institutions (Financial Technology) in Indonesia - Frontieka Ayu Rahmanto; Hanifah Fauziyah; Farah Afifatun Nasikhah; Noviana Pramesti; Jasmine Fahira Maulana; Alviana Ayu Nurhidayah (Proceeding International Conference Restructuring and Transforming Law, 2023)
Nowadays, technological developments are increasingly rapid, extending to digital-based financial institution services or financial technology (fintech). Fintech emerged to provide financial services easily and efficiently to receive a product or related loan funds. The Financial Services Authority (OJK) as an independent institution that supervises the financial sector has an important role in expanding and improving its supervision of digital-based financial institutions as an effort to protect consumers. This research uses normative juridical research methods, namely analyzing positive legal rules and norms related to OJK such as Law no. 21 of 2011 concerning the Financial Services Authority and Financial Services Authority Regulations (POJK) and this research is descriptive because it explains the picture regarding the role of the OJK as a supervisory institution regarding the growth of innovation in technology-based financial services. In carrying out its role, OJK uses two methods, namely pre-operational business methods which are related to before fintech is created and methods during business operations which are related to fintech when it has been implemented. In such a way, the regulations that have been made must be carried out appropriately to protect the interests and security of users.